Construction of cross-linked PEO grafting copolymer for high-performance gel electrolyte - Shuangshuang Wang; Huizi Zhang; Jilu Ma; Dejia Liu; Tonghui Zhang; Yuchao Li; Guang Li (Polymer Testing)
It is an urgent demand of polyethylene oxide with poor crystallinity, high electrolyte affinity and ionic conductivity in portable electronics usage. In the present work, crosslinked poly (glycidyl methacrylate) (PGMA) grafting modified PEO has been prepared. Firstly, PGMA with controlled chain length can be highly efficient covalent anchored on PEO main chain with the assistance of N-hydroxyphthalimide (NHPI) catalysis combined with activators regenerated by electron transfer ATRP (ARGET-ATRP). Then the grafted PGMA chains undergone crosslinked process in the presence of 4, 4-diaminodiphenyl sulfone (DDS) to produce crosslinked PEO-g-PGMA (C-PEO-g-PGMA) film. The film could be used in electronic devices, and it exhibit amorphous structure, higher electrolyte wettability and mechanical strength compared to that of pure PEO. Moreover, the performance for electrical double-layer capacitor (EDLC) assembled with electrolyte-soaked C-PEO-g-PGMA films were sharply higher than that of EDLC with PEO. The present study provides a novel and highly efficient methodology for the modification of poly (ethylene oxide) (PEO) through crosslinked grafting side chains.